2017
DOI: 10.2337/dc17-0654
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy in the Treatment of Ischemic Lower- Extremity Ulcers in Patients With Diabetes: Results of the DAMO2CLES Multicenter Randomized Clinical Trial

Abstract: Additional HBOT did not significantly improve complete wound healing or limb salvage in patients with diabetes and lower-limb ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
132
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 22 publications
0
132
1
5
Order By: Relevance
“…Taken together, the study by Santema et al (1) showed that a more realistic treatment effect with a larger sample size, along with better matched groups, could have led to significant results in favor of HBOT.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Taken together, the study by Santema et al (1) showed that a more realistic treatment effect with a larger sample size, along with better matched groups, could have led to significant results in favor of HBOT.…”
mentioning
confidence: 93%
“…On closer look at the data in Table 2 in Santema et al (1), readers will notice that the lower bound of the 95% CI in the risk difference column (particularly for limb salvage, amputation-free survival, freedom from amputations index limb, and overall mortality) is very close to 0, meaning that should the study be completed with the initially calculated sample size (n 5 226), the lower bound would probably be above the threshold of statistical significance, i.e., 0.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…They both express concerns regarding our conclusion based on the results of the DAMO 2 CLES [Does Applying More Oxygen (O 2 ) Cure Lower Extremity Sores?] trial that hyperbaric oxygen therapy (HBOT) does not confer benefit in the treatment of patients with ischemic foot ulcers and diabetes (3).…”
mentioning
confidence: 99%
“…study (1) is the only prospective multicenter trial evaluating the effectiveness of hyperbaric oxygen therapy (HBOT) in the treatment of ischemic diabetic foot ulcers (DFUs). By involving 10 hyperbaric facilities across the Netherlands and Belgium, this protocol captures a cross-section of the standard care (SC) in the region with regard to ischemic DFUs but falls victim to variable clinical practice patterns.…”
mentioning
confidence: 99%